SISTEM INFORMASI RESERVASI DAN PEMASARAN AGROEDUTOURISM PADA ALAM MAIMBAU ADVENTURE BERBASIS WEB - Fitratul Azimah; Rahmadini Darwas; Ilfa Stephane; Ade Irma Suryani (Ensiklopedia of Journal, 2023)
This study aims to build an agroedutourism reservation and marketing information system at Alam Maimbau adventure in processing data, making tour package reservation reports and doing marketing. The problem faced by Alam Maimbau Adventure is that there is no system that can display tour package information along with the reservation process so that interesting tour packages owned by Alam Maimbau Adventure are not known by guests or potential tourists. In addition, the management of tour package data has not been managed properly, causing the information that is not received completely by guests. The method used in this study is the prototype method. This research produces a reservation and marketing information system that makes it easier for admins to manage guest data. In addition, with this information system, guests can find information about tourist objects in West Sumatra that were not known before.